다중 리플로우에 따른 Sn-Cu-(X)Al-(Y)Si/Cu 접합부 특성 연구 - 유동열(Dong-Yurl Yu); 손준혁(Jun-Hyuk Son); 고용호(Yong-Ho Ko); 이창우(Chang-Woo Lee); 변동진(Dongjin Byun); 방정환(Junghwan Bang) (대한용접·접합학회지, 2020)
Joint properties of Sn-Cu-(X)Al-(Y)Si lead-free solder alloy were investigated for automotive electronics module. In this study, Sn-0.5Cu-(0.01, 0.03)Al-0.005Si(wt.%) alloys were then fabricated in the form of solder balls for reflow samples. To evaluation of solder joint properties, solder ball was attached to PCB finished with OSP Cu pad. The reflow process was performed for 40 s above 260.5 ℃. And solder joint was evaluated by repeating the reflow process up to 10 times. The melting temperatures of Sn-0.7Cu, 0.01 Al- 0.005Si and 0.03Al-0.0.005Si were 227.5, 230.2 and 231.4 ℃, respectively. Initial microstructures are composed of β-Sn regions surrounded by eutectic networks with spherical Cu6Sn5 IMC particles. However, with the increasing Al content, refined eutectic β-Sn + Cu-Sn IMC networks were observed. The shear strength of Sn-0.5Cu-0.03Al-0.005Si solder joints was higher than Sn-0.5Cu-0.01Al-0.005Si and Sn-0.7Cu solder after 10 reflow test. KCI Citation Count: 0